Evaluating Policy and Planning Tools for Healthy Corner Stores. - Lazer, Leah S. (Tufts Archival Research Center, 2014)
Abstract: This research explores the ways that urban healthy corner stores can improve food environments in low-income areas, counteracting the disparities in food access that contribute to rising U.S. rates of obesity and diet-related disease. Corner stores are often locally-owned businesses that are already equipped for food retail and are already frequented by neighborhood residents, making them more responsive to community preferences and more cost-effective than supermarket attraction strategies. Accordingly, cities and organizations are implementing “healthy corner store programs” to support the stores in selling healthy food, improving neighborhood livability and local business development. Based on a literature review and practitioner interviews, I assess the strengths and challenges of healthy corner store programs, review policy and planning tools to support these programs, and propose program evaluation methods to measure their outcomes. I find that most healthy corner store programs are still in initial phases, inviting innovation and expansion in coming years, which would be bolstered by more rigorous program evaluations. These initiatives can have most significant impacts as part of larger multi-pronged strategies to increase food access, and would be more institutionally sustainable if policy or planning approaches eventually replaced current resource-intensive programs.